A Novel w-Transform of Bicomplex numbers and their properties - C V Rao (Utilitas Mathematica, 2024)
In this paper, I have derived a new w-Transform similar to z-transform of Bicomplex number. Also, I have derived some useful properties in W-Transform of Bicomplex numbers. I have solved w-transform of some standard sequences. I hope these results highly useful in the field of Electrical and electronics engineering fields.